Expediting genome synthesis of Corynebacterium glutamicum with an artificial chromosome vector - Zhang, Zhanhua; Hong, Peixiong; Li, Zebin; Li, Baitao; Chen, Tai; Shen, Yue; Yang, Xiaofeng; Ye, Yanrui; Wang, Yun; Lin, Zhanglin (Trends in biotechnology (Regular ed.), 2025)
An artificial chromosome-like plasmid was developed for Corynebacterium glutamicum.The C. glutamicum artificial chromosome facilitates stepwise genome replacements of ~50 kb.In total, 361 kb of synthetic DNA was integrated into the C. glutamicum genome (11%). Recent advances in genome synthesis have relied on scalable DNA assembly and delivery, and efficient recombination techniques. While these methods have enabled rapid progress for Escherichia coli and yeast, they are often inadequate for other microorganisms. Here, we devised a Corynebacterium glutamicum artificial chromosome (CAC), which combines a replicating system from a closely related strain with an innate partitioning system. This CAC vector can efficiently deliver DNA fragments up to 56 kb and maintain stability in C. glutamicum. Leveraging the CAC vector, we developed CAC Excision Enhanced Recombination (CACEXER), a streamlined strategy for iterative genome replacements in C. glutamicum. Using this approach, we integrated 361 kb (11%) of synthetic DNA into the genome, creating semi-synCG-A. This strain paves the way to establish C. glutamicum as the third industrial microorganism, alongside E. coli and Saccharomyces cerevisiae, to undergo large-scale genome synthesis. [Display omitted] This work establishes a bacterial artificial chromosome (BAC)-like vector for Corynebacterium glutamicum and introduces the streamlined C. glutamicum Artificial Chromosome (CAC) Excision Enhanced Recombination (CACEXER) strategy for de novo genome synthesis of this industrially important Gram-positive microbe. To date, we have successfully integrated 361 kb (or 11%) of synthetic DNA into the genome. To further enhance this CAC-based approach and accelerate genome synthesis, we aim to incorporate recent advancements in large-scale DNA assembly and delivery. In addition, genome debugging to mitigate growth defects will be crucial for achieving a fully synthetic C. glutamicum genome. Based on our current progress, we propose that this technology has reached a Technology Readiness Level (TRL) between 3 and 4, as defined by NASA. We developed an artificial chromosome plasmid (CAC) for large-scale genome replacement of Corynebacterium glutamicum, accelerating the genome synthesis for this organism. This work offers design principles for advancing de novo genome design and synthesis for industrially relevant Gram-positive microbes.